Photodynamic therapy and associated targeting methods for treatment of brain cancer - Bartusik-Aebisher, Dorota; Serafin, Iga; Dynarowicz, Klaudia; Aebisher, David (Frontiers in Pharmacology, 2023)
Brain tumors, including glioblastoma multiforme, are currently the a cause of suffering and death of hundreds tens of thousands of people around the worldwide. Despite the progress of medicineadvances in clinical treatment, the average patient survival time from the moment of diagnosis of GBM glioblastoma multiforme with the use ofand application of standard treatment methods, such as surgical resection, radio-and chemotherapy, is less than 15 months4 years. The continuing development of new therapeutic methods for targeting and treating brain tumors may extend life and provide greater comfort to patients. One such of thedeveloping therapeutic methods is photodynamic therapy. Photodynamic therapy is currently a progressive method of therapy , not only for anti-cancer. It is also used in dermatology, dentistry, ophthalmology, and has found use has a bactericidal effectas an antimicrobial agent. It has also found wide application in diseases of the head and neck, both inphotodiagnosis. diagnosis and treatment. First of all, itPhotodynamic therapy requires the presence of three necessary substratescomponents: a clinically approved photosensitizer, oxygen and light. of the appropriate wavelength. The This paper reviews is a review of selected the literature of works from Pubmed and , Scopus and ScienceDirect scientific databases in the field of photodynamic therapy in brain tumors (mainly gliomas)with an emphasis on glioblastoma treatment.